A Comparison of Physical Soil Organic Matter Fractionation Methods for Amended Soils - Sarah Duddigan; Liz J. Shaw; Paul D. Alexander; Chris D. Collins (Applied and Environmental Soil Science)
Selecting a suitable physical fractionation method, to investigate soil organic matter dynamics, from the plethora that are available is a difficult task. Using five different physical fractionation methods, on soils either nontreated or with a history of amendment with a range of exogenous organic matter inputs (Irish moss peat; composted horse manure; garden compost) and a resulting range of carbon contents (6.8 to 22.2%), we show that method selection had a significant impact on both the total C recovered and the distribution of the recovered C between unprotected, physically protected, or chemically protected conceptual pools. These between-method differences most likely resulted from the following: (i) variation in the methodological fractions obtained (i.e., distinguishing between aggregate size classes); (ii) their subsequent designation to conceptual pools (e.g., protected versus unprotected); and (iii) the procedures used in sample pretreatment and subsequent aggregate dispersion and fractionation steps. The performance of each method also varied depending on the amendment in question. The findings emphasise the need for an understanding of the nature of the soil samples under investigation, and the stabilisation mechanism of interest, both prior to method selection and when comparing and interpreting findings from literature studies using different fractionation methods.